The impact of surface acting on coworker-directed voluntary workplace behaviours. Issue 3 (3rd May 2016) - Yue, Yumeng; Wang, Karyn L.; Groth, Markus
Abstract : The effects of emotional labour, that is, managing one's emotions for work, not only predict a range of intrapersonal and organizational outcomes but can also spillover to affect non-work relationships. Despite this, relatively little is known about whether the performance of surface acting affects behaviours towards more proximal organizational members, how this occurs, and the role of supportive relationships in influencing this relationship. In this article, we examine the relationships between surface acting, state positive and negative affect, and co-worker support on co-worker-directed interpersonal behaviours in the workplace. Survey data collected at multiple time points suggest a moderated mediation model, in which surface acting interacts with co-worker support to influence employees' voluntary behaviours through state affect. Specifically, our findings suggest that surface acting increases subsequent engagement in deviance behaviours by increasing the experience of negative affective states, especially when co-worker support is low. Surface acting also decreases the subsequent engagement of organizational citizenship behaviour through decreasing the experience of positive affective states. We conclude with a discussion of how surface acting can consequently lead to negative spirals in the organization and the implications of this for practice.